SHM of Reinforced Concrete Elements by Rayleigh Backscattering DOFS - Barrias, António; Casas, Joan R.; Villalba, Sergi (Frontiers in Built Environment, 2019)
This document showcases the latest research conducted within UPC – BarcelonaTech on the performance of distributed optical fiber sensors (DOFS), more specifically the case of the optical backscattered reflectometry (OBR) system, in the structural health monitoring (SHM) of bridges and large scale structures. This technology has demonstrated promising results for monitoring applications in a wide range of fields but due to its novelty, still presents several uncertainties which prevent its use in a more systematic and efficient way in civil engineering infrastructures, being this even more evident in the case of concrete structures. Therefore, different laboratory experimental campaigns were devised where multiple aspects of the instrumentation of DOFS technology in civil engineering applications were assessed and scrutinized. Such as the study of new implementation methods, comparison and performance analysis of different bonding adhesives and spatial resolution. Additionally, the fatigue performance of this sensing typology was also assessed. Furthermore, the use of the OBR system technology was applied in a real world structure in Barcelona, Spain, where new challenging conditions had to be addressed. Consequently, with this work, different conclusions are obtained related to the proficiency and limitations on the use of this particular type of optical sensing system in concrete structures.